Thwarted Interpersonal Needs and Suicide Ideation Distress Among Psychiatric Inpatients: The Moderating Role of Criminal Associates. (September 2019) - Mitchell, Sean M.; Cukrowicz, Kelly C.; Roush, Jared F.; Brown, Sarah L.; Alquist, Jessica L.; Bolaños, Angelea D.; Morgan, Robert D.; Poindexter, Erin K.
Psychiatric inpatients are at elevated risk of suicide, and approximately half are criminal justice-involved. Their involvement with criminal associates may be linked to increased suicide ideation distress; however, this has not been examined. This study tested main effects of, and interactions between, thwarted belongingness (TB) or perceived burdensomeness (PB), time spent with associates, and associates' criminal involvement predicting suicide ideation distress. In our study, psychiatric inpatients ( n = 139) completed assessments cross-sectionally. Results indicated that TB, PB, and associates' criminal involvement were significantly related to greater suicide ideation distress. A significant three-way interaction indicated participants who endorsed high TB, spent more time with associates, and had associates high in criminal involvement had the greatest probability of "Extreme" suicide ideation distress. These findings suggest that spending time with criminal associates may increase suicide ideation distress more than not having social interactions. Implications and limitations of this study are discussed.